Catheter-Associated Infections: Pathogenesis Affects Prevention - Trautner, Barbara W. (2004)
Intravascular catheters and urinary catheters are the 2 most commonly inserted medical devices in the United States, and they are likewise the two most common causes of nosocomially acquired bloodstream infection. Biofilm formation on the surfaces of indwelling catheters is central to the pathogenesis of infection of both types of catheters. The cornerstone to any preventive strategy of intravascular catheter infections is strict attention to infection control practices. Antimicrobial-impregnated intravascular catheters are a useful adjunction to infection control measures. Prevention of urinary catheter–associated infection is hindered by the numbers and types of organisms present in the periurethral area as well as by the typically longer duration of catheter placement. Antimicrobial agents in general have not been effective in preventing catheter-associated urinary tract infection in persons with long-term, indwelling urethral catheters. Preventive strategies that avoid the use of antimicrobial agents may be necessary in this population.